Polymorphous adenocarcinoma of the upper lip: challenges in diagnosing a malignant lesion presenting benign clinical appearance - Tomazelli, Karin Berria; Bianco, Bianca Carla; Oliveira , Karen Corrêa de; Silva , Felipe de Borba Chiaramonte; Rivero , Elena Riet Correa; Rabelo , Gustavo Davi; Grando , Liliane Janete (Journal of Oral Diagnosis, 2025)
Polymorphous Adenocarcinoma (PAC) is a distinctive malignancy that primarily affects the minor salivary glands. A defiant diagnosis of this lesion is related to its pathological findings, including architectural diversity, and its clinical aspect that usually mimics benign lesions. A 72-year-old male presented a slow-growing painless nodule in the upper lip with two years of evolution. An excisional biopsy was performed, and despite the first clinical impression of a benign condition, the histopathological analysis confirmed PAC. The immunohistochemical analysis showed positive expression for CKAE1/AE3, CK7, S100 and p63, and negative for SMA, CK20 and p40 distinguishing this case from other salivary gland tumors. In addition, the lesion usually affects the palate, revealing an atypical site of occurrence for this case. The patient was referred to a Head and Neck surgeon to ensure a second surgical intervention to include margin extension. One year follow-up reveals no signs of recurrence. This case highlights the need for clinicians to consider malignancies in lesions with a clinical aspect usually common to benign conditions. In addition, the unexpected PAC occurrence in the upper lip was emphasized. This case report reinforces the PAC clinical appearance diversity and its microscopic features, accompanied by a unique immunohistochemical profile.